2013
DOI: 10.1111/jnc.12229
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cβ is a modulator of the dopamine D2 autoreceptor‐activated trafficking of the dopamine transporter

Abstract: The strength and duration of extracellular dopamine concentrations are regulated by the presynaptic dopamine transporter (DAT) and dopamine D2 autoreceptors (D2autoRs). There is a functional interaction between these two proteins. Activation of D2autoRs increases DAT trafficking to the surface whereas disruption of this interaction compromises activities of both proteins and alters dopaminergic transmission. Previously we reported that DAT expression and activity are subject to modulation by protein kinase Cβ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 47 publications
1
63
1
Order By: Relevance
“…However, further work exploring PKC isoform specificity for DAT regulation points to a greater complexity of enzymes and actions. Thus, studies conducted with the PKCb specific inhibitor LY379196 [8((dimethylamino)methyl)-6,7,8,9,10,11-hexahydro-5,21:12,17-dimetheneo-18H-dibenzo(i,o) pyrrolo (3,4-1)(1,8)diazacyclohexandecine-18,10(19H) dione] as well as kinase knockout mice support a role for PKCb in DAT regulation, although distinct from that observed in studies with phorbol ester stimulation, Chen et al (2013) observed that treatment of mouse striatal synaptosomes with LY279196 blocked the ability of the D2 agonist quinpirole to increase DAT surface levels and DA uptake, suggesting a role for PKCb in supporting elevated surface expression. LY279196 also blocked quinpirole-induced increases in p-extracellular signal-related kinase 1/2 (ERK1/2).…”
Section: Protein Kinase C-overviewmentioning
confidence: 92%
See 3 more Smart Citations
“…However, further work exploring PKC isoform specificity for DAT regulation points to a greater complexity of enzymes and actions. Thus, studies conducted with the PKCb specific inhibitor LY379196 [8((dimethylamino)methyl)-6,7,8,9,10,11-hexahydro-5,21:12,17-dimetheneo-18H-dibenzo(i,o) pyrrolo (3,4-1)(1,8)diazacyclohexandecine-18,10(19H) dione] as well as kinase knockout mice support a role for PKCb in DAT regulation, although distinct from that observed in studies with phorbol ester stimulation, Chen et al (2013) observed that treatment of mouse striatal synaptosomes with LY279196 blocked the ability of the D2 agonist quinpirole to increase DAT surface levels and DA uptake, suggesting a role for PKCb in supporting elevated surface expression. LY279196 also blocked quinpirole-induced increases in p-extracellular signal-related kinase 1/2 (ERK1/2).…”
Section: Protein Kinase C-overviewmentioning
confidence: 92%
“…As noted earlier, progress in the study of PKC mechanisms that regulate DAT will likely depend on the identification of receptor-mediated signaling pathways that rely on PKC signaling. As noted above, PKCb isoforms have been reported to play a role in D2 receptor-mediated trafficking of DAT (Chen et al, 2013), possibly connected to DAT via ERK1/2 (see below). Additionally, Page et al (2001) reported that an mGluR agonist decreases DA uptake in rat striatal synaptosomes, an effect that can be blocked by the PKC inhibitor …”
Section: Regulation Of Dopamine Transporter Membranementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is possible that changes in the interaction of the DAT protein with downstream effectors responsible for these post-translational modifications are altered following self-administration in a way that changes the ability of ligands to bind to the DAT and inhibit the clearance of DA. In addition, the DAT has been shown to form oligomer complexes (Hastrup et al, 2003) and be modulated by receptors such as the D2 autoreceptor (Chen et al, 2013), which are two additional mechanisms that could have a role in the observed changes in cocaine potency.…”
Section: Discussionmentioning
confidence: 99%